Earth as construction material in the circular economy context: practitioner perspectives on barriers to overcome. (27th September 2021) - Morel, Jean-Claude; Charef, Rabia; Hamard, Erwan; Fabbri, Antonin; Beckett, Chris; Bui, Quoc-Bao
Abstract : The need for a vast quantity of new buildings to address the increase in population and living standards is opposed to the need for tackling global warming and the decline in biodiversity. To overcome this twofold challenge, there is a need to move towards a more circular economy by widely using a combination of alternative low-carbon construction materials, alternative technologies and practices. Soils or earth were widely used by builders before World War II, as a primary resource to manufacture materials and structures of vernacular architecture. Centuries of empirical practices have led to a variety of techniques to implement earth, known as rammed earth, cob and adobe masonry among others. Earth refers to local soil with a variable composition but at least containing a small percentage of clay that would simply solidify by drying without any baking. This paper discusses why and how earth naturally embeds high-tech properties for sustainable construction. Then the potential of earth to contribute to addressing the global challenge of modern architecture and the need to re-think building practices is also explored. The current obstacles against the development of earthen architecture are examined through a survey of current earth building practitioners in Western Europe. A literature review revealed that, surprisingly, only technical barriers are being addressed by the scientific community; two-thirds of the actual barriers identified by the interviewees are not within the technical field and are almost entirely neglected in the scientific literature, which may explain why earthen architecture is still a niche market despite embodying all the attributes of the best construction material to tackle the current climate and economic crisis. This article is part of the theme issue 'The role of soils in delivering Nature's Contributions to People'.